Central Nervous System-Derived Exosomal Alpha-Synuclein in Serum May Be a Biomarker in Parkinson's Disease. (10th August 2019) - Si, Xiaoli; Tian, Jun; Chen, Yanxing; Yan, Yaping; Pu, Jiali; Zhang, Baorong
Abstract: Parkinson's disease (PD) is a common movement disorder. Alpha-synuclein (α-synuclein) plays a critical role in PD. In this study, we evaluated the level of central nervous system (CNS)-derived exosomal α-synuclein in serum, which may be regarded as a specific peripheral biomarker for PD. We recruited patients with PD in the early stage along with essential tremor (ET), and we recruited age- and gender-matched healthy subjects as healthy controls (HC). We divided patients with PD into the tremor-dominant (TD) group and the non-tremor-dominant (NTD) group. We evaluated the levels of α-synuclein in CNS-derived exosomes in serum samples. As a result, there was a significant difference between four groups (p < 0.05). This level was lower in the PD group than in the ET and HC groups (p < 0.05). Among the PD group, this level was lower in the NTD group than in the TD group (p < 0.05). Furthermore, the performance of serum CNS-derived exosomal α-synuclein was found to moderately aid in PD diagnosis (AUC = 0.675, p < 0.05) and had a potential to diagnose NTD (AUC = 0.761, p < 0.05). Therefore, CNS-derived exosomal α-synuclein in the serum may be regarded as a biomarker to identify PD from ET and HC in the early stage. It may also be used to identify different motor types in PD. The pathogenesis of PD in different motor types may be different, which needs further research. Highlights: We detected CNS derived exosomal α-synuclein in serum as a biomarker for PD. The quantity of serum CNS-exosome α-syn of PD is lower than ET and HC (P < 0.05). The quantity of serum CNS-exosome α-syn is NTD (P < 0.05) < TD (P > 0.05) < ET and HC. The level of serum CNS-exosome α-syn may have moderate potential to diagnose PD. The level of serum CNS-exosome α-syn may have great potential to diagnose NTD.